Facial Anthropometric Measurements and Principles – Overview and Implications for Aesthetic Treatments - Armengou, Xavier; Frank, Konstantin; Kaye, Kai; Brébant, Vanessa; Möllhoff, Nicholas; Cotofana, Sebastian; Alfertshofer, Michael (Facial Plastic Surgery, 2023)
Facial anatomy is highly individual in each patient. Anthropometric measurements can be a useful tool to objectively analyze individual facial anatomy to allow for better comparability before and after treatments to ultimately improve standardization of facial procedures, both nonsurgical and surgical. The aim of this study was to provide a comprehensive overview over clinically relevant and feasible facial anthropometric measurements and principles for aesthetic medicine. A literature review was conducted to describe the most important and clinically relevant anthropometric measurements and principles for both the entire face and for three aesthetically relevant facial regions: the periorbital region, the nose, and the perioral region. A multitude of different anthropometric measurements and principles have been described in the literature for both the overall facial appearance and specific facial regions. Certain generally accepted anthropometric principles and proportions need to be respected to achieve aesthetic and harmonious results. For the overall facial appearance, a focus on symmetry, certain proportions, facial angles, and indices has been described. Principles and measurements were also described for the periorbital region, the nose, and the perioral region. Although attractiveness and aesthetic perception are subjective, objective evaluation of facial surface anatomy via anthropometric measurements can improve pre- and postinterventional analysis of the face and help the treating physician to individualize treatments, both nonsurgical and surgical.
Keywords: facial anthropometry; anthropometric measurements; aesthetic procedures; facial anatomy; facial landmarks